STUDI FAKTOR-FAKTOR PENYEBAB KEMISKINAN MASYARAKAT DESA LOHIA KECAMATAN LOHIA KABUPATEN MUNA - Sartika, Cica; Balaka, M.Yani; Rumbia, Wali Aya (JURNAL EKONOMI UHO, 2016)
This study aims to find out  the characteristic poor poeple in Lohia Village, Muna Regency. Data used is primary and secondary data. Primary data collected  through questionare from 45 respondent.  Respondent is determined  by purposive sampling based on homogen characteristic.  Data analyzed  with  descriptive. The  results show that  poor poeple in Lohia Village is characterized  by: productive age, the higer  number of family members,  the  lower education and skill, lower income,  lack of production factors  and the lower of work ethic.